Histomorphometric Analysis of Umbilical Arteries in Preeclampsia - Ali, Saleena N; H Y, Suma; Sontakke, Yogesh Ashok; Maurya, Dilip Kumar (Academia Anatomica International, 2019)
Introduction: Preeclampsia is a pregnancy?related hypertensive disorder complicated with placental hypoxia and resistance. The hypoxia and hypertension can induce changes in the morphometric parameters of umbilical cord and its vessels that can further affect the blood flow to the fetus. Subjects and Methods: Umbilical cords were collected from new-borns of preeclamptic and normal mothers, length and diameter were measured. Further, cords were processed for histological examination. The diameter, luminal area and wall thickness of umbilical arteries were measured. Results: A shorter and narrower cord was observed in preeclampsia. The umbilical arteries in preeclamptic cases were dilated, whereas statistically significant changes were not observed in the thickness of wall. Conclusion: Dilated umbilical arteries would be an adaptation to the affected babies so as to ensure reduced resistance for fetal circulation.